2006
DOI: 10.1002/ijc.21729
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of colitis‐associated carcinogenesis in a mouse model by diet supplementation with ursodeoxycholic acid

Abstract: Bile acids in the intestinal lumen contribute to the homeostatic regulation of proliferation and death of the colonic epithelial cells: Deoxycholic acid (DCA) appears to enhance and ursodeoxycholic acid (UDCA) to attenuate the process of chemically induced carcinogenesis. We studied the effects of UDCA on colitis-related colorectal carcinogenesis. Three groups of 25 mice were given 0.7% dextran sulphate in drinking water for 7 days and pure water for 10 days and were fed a standard diet containing double iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…24,25 In addition, UDCA reduces carcinogenesis in several pre-malignant conditions of liver and colon in a rodent model. [26][27][28][29] Furthermore, recurrence of colorectal adenomas with highgrade dysplasia in a phase III trial was shown to be decreased after treatment with UDCA. 30 Although the tumor suppressive activity of UDCA is believed to be linked to the induction of apoptosis and cell cycle arrest, and the inhibition of oncogenic factors including Ras and COX-2, in human cancer cell lines, [31][32][33] these mechanisms are not yet fully understood.…”
mentioning
confidence: 99%
“…24,25 In addition, UDCA reduces carcinogenesis in several pre-malignant conditions of liver and colon in a rodent model. [26][27][28][29] Furthermore, recurrence of colorectal adenomas with highgrade dysplasia in a phase III trial was shown to be decreased after treatment with UDCA. 30 Although the tumor suppressive activity of UDCA is believed to be linked to the induction of apoptosis and cell cycle arrest, and the inhibition of oncogenic factors including Ras and COX-2, in human cancer cell lines, [31][32][33] these mechanisms are not yet fully understood.…”
mentioning
confidence: 99%
“…Separately, it is well established that inflammatory disorders, such as ulcerative colitis, may also lead to colon cancer in the long run (18). Interestingly, the chronic model of DSS-induced colitis can eventually result in colon carcinogenesis, with animals exhibiting intestinal neoplasia similar to that seen in human disease (38). Thus it is not surprising that this preclinical model of colitis has been extensively utilized for studying the pathophysiological mechanisms of disease and assessing the efficacy of potential treatments for ulcerative colitis (16,57).…”
Section: Discussionmentioning
confidence: 99%
“…UDCA feeding resulted in a highly significant inhibition of colorectal cancer and adenoma formation in the azoxymethane rat model (Earnest et al, 1994). UDCA supplementation suppressed colitisassociated carcinogenesis in a dextran sulphate sodium mouse model (Loddenkemper et al, 2006). In a rodent model of cholestasis, the administration of 24-norUrsodeoxycholic acid (norUDCA) to Mdr2 knockout mice improved sclerosing cholangitis (Fickert et al, 2006).…”
Section: Introductionmentioning
confidence: 99%